Gangguan Tingkah Laku pada Siswa SMA dan Pondok Pesantren Terpadu Menggunakan Kuesioner Kekuatan dan Kesulitan (SDQ) - Adhyka, Nurmaines; Arwin, Popy; Ramadoni, Ramadoni; Huvaid, Sevilla Ukhtil (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2025)
The Strengths and Difficulties Questionnaire (SDQ) is widely used to screen for mental health problems in children and adolescents aged 4–18. Adolescents’ behavioral responses to challenges may differ based on their living environment, such as living with parents or in a boarding school. This study aimed to compare the mental health status of general high school students and integrated Islamic boarding school students in two cities in West Sumatra, Indonesia. A cross-sectional study was conducted involving 120 students aged 15–17 years selected through incidental random sampling. SDQ data were collected online in public schools and using printed questionnaires in boarding schools. Independent t-tests were used for analysis. Significant differences were found in conduct problems (p = 0.010) and peer relationship problems (p = 0.046). Strong correlations were identified between conduct problems and hyperactivity (r = 0.289**), as well as between peer problems and emotional symptoms (r = 0.295**) and hyperactivity (r = 0.356**). Social environments, including parenting patterns and limited parental interaction, play a crucial role in adolescent mental health. This study provides empirical evidence on how differences in school systems and living arrangements affect students' psychological conditions, supporting school-based mental health interventions.